Peran Masyarakat dalam Pengelolaan Tanah Wakaf untuk Pendidikan Islam (Studi pada Desa Jumat Kecamatan Talang Empat) - Cindy Ameilia Utami; Asnaini; Andi Harpepen (Universitas Muhammadiyah Surabaya, 2026)
This study aims to describe the role of the community of Jumat Village in managing waqf land for Islamic education through Madrasah Aliyah Muslim Cendikia, to analyze its contribution to adolescent behavior, and to identify the challenges faced in its management. This study employs a qualitative approach with a case study design focusing on social phenomena in Jumat Village, Talang Empat District, Bengkulu Tengah Regency, Bengkulu Province, Indonesia. Data were collected through interviews, observations, and documentation involving the chairperson of the foundation, teachers, alumni, village officials, and community members. Data analysis was conducted using the interactive model of Miles and Huberman. The findings indicate that the community has played an active role from the initial waqf process and construction stage to the ongoing management of the madrasah through mutual cooperation, financial support, voluntary services, and social supervision. This participation supports the sustainability of Islamic education and has a positive impact on the moral development and behavior of adolescents. The challenges identified relate to limited funding and resource support in optimizing waqf management.